Influence of by-product material and calcined pozzolan on some geotechnical characteristics of cement treated fine-grained soil: Comparative study - Jawad, Ibtehaj Taha; Jafer, Hassnen Mosa; Majeed, Zaid Hameed (Edelweiss Applied Science and Technology, 2025)
Stabilizing unstable soil is a significant challenge in civil engineering, especially in regions with soft clay. This study examines the compaction and strength properties of stabilized soils incorporating calcined kaolin clay (CKC), Portland cement (PC), and marble dust powder (MDP). Two binder systems were developed: PC-CKC and PC-MDP, and their performance was evaluated through compaction, Atterberg limits, and unconfined compressive strength (UCS) tests. Soil treatments involved adding 3% PC with varying percentages (3%, 6%, and 9%) of CKC or MDP, based on previous studies identifying 3% PC as optimal. UCS specimens were cured for 3, 7, and 28 days to assess strength development. The results showed that both CKC and MDP enhanced the geotechnical properties of cement-stabilized soils. However, CKC outperformed MDP in reducing the plasticity index and increasing UCS values. These findings highlight the potential of calcined kaolin clay as a sustainable additive for soil stabilization, offering a long-term solution for recycling industrial by-products and improving the performance and durability of infrastructure projects.